2006
DOI: 10.1016/j.vaccine.2006.01.061
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro immune response model to determine tetanus toxoid antigen (vaccine) specific immunogenicity: Selection of sensitive assay criteria

Abstract: Many vaccines employed in childhood vaccination programmes are produced by conventional techniques, resulting in complex biological mixtures for which batch-related quality control requires in vivo potency testing. Monitoring consistency via in vitro tests during the vaccine production has the capacity to replace certain of the in vivo methods. In this respect, determining vaccine antigen immunogenicity through functional immunological tests has high potential. Advances in immunology have made it possible to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…All of these express CD172a, and in a model of antigen presentation of inactivated foot-and-mouth disease virus (FMDV) to T lymphocytes the activation was dependent on the presence of CD172a + cells [40,41]. Similar results were also obtained with classical swine fever virus (CSFV) and protein antigens derived from this virus [25,42], as well as with tetanus toxoid [43]. Separating the CD172a + PBMC into a major population of CD14 + monocytes and a minor population of CD14 À cells showed that the latter contained the CD4 À blood cDC along with the CD4 + pDC ( Table 1; [40]).…”
Section: Blood DCmentioning
confidence: 61%
“…All of these express CD172a, and in a model of antigen presentation of inactivated foot-and-mouth disease virus (FMDV) to T lymphocytes the activation was dependent on the presence of CD172a + cells [40,41]. Similar results were also obtained with classical swine fever virus (CSFV) and protein antigens derived from this virus [25,42], as well as with tetanus toxoid [43]. Separating the CD172a + PBMC into a major population of CD14 + monocytes and a minor population of CD14 À cells showed that the latter contained the CD4 À blood cDC along with the CD4 + pDC ( Table 1; [40]).…”
Section: Blood DCmentioning
confidence: 61%
“…The immune response against TT is characterized by strong differentiation of T cells and high production of IFN‐γ after vaccination . It was determined in vitro that the TT‐specific IFN‐γ secretion was mediated exclusively by CD4 + T cells [T helper type 1 (Th1) response] . An adequate amplification of the immune response of T cells and a potent IFN‐γ production are fundamental to B cell differentiation and suitable production of anti‐TT IgG .…”
Section: Introductionmentioning
confidence: 99%
“…To test whether differences in uptake of functionalized SAGE affected downstream antigen‐specific responses, the proliferative ability of human PBMCs was determined after exposure to each of the three TT‐functionalized SAGEs for up to 7 d (Figure b). PBMC proliferation is indicative of a T cell response and, in this case, considered to be a CD4 + T cell response against the TT peptide, a model CD4 + T cell epitope . Experimental controls of parent SAGE, free TT peptide, and parent SAGE mixed with free TT peptide elicited low levels of cellular proliferation.…”
Section: Resultsmentioning
confidence: 99%